2005
DOI: 10.1002/mmnz.200310001
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the genus Spiophanes (Polychaeta, Spionidae); with new synonymies, new records and descriptions of new species

Abstract: Thep aper presents ac omprehensive revision of the genus Spiophanes (Polychaeta, Spionidae) based on type material. The identity of Spiophanes kroyeri,t he type species of the genus,i sf ixed by lectotype designation. Enhanced diagnoses with illustrations,n otes on their distribution and comments on species identification for all valid species are provided. S. chilensis Hartmann-Schröder,1 965 and S. söderströmi Hartman, 1953 are synonymized with S. duplex (Chamberlin, 1919). S. kroyeri reyssi Laubier,1 964 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 6 publications
0
47
0
Order By: Relevance
“…They have already been proven extremely useful diagnostic characters in other spionid genera, e.g. in Marenzelleria (Bick 2005), Spiophanes (Meißner 2005), and Laonice (Sikorski 2002). The nuchal organs of Spio species from the North and Baltic Seas consists of two median and two lateral bands of cilia (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…They have already been proven extremely useful diagnostic characters in other spionid genera, e.g. in Marenzelleria (Bick 2005), Spiophanes (Meißner 2005), and Laonice (Sikorski 2002). The nuchal organs of Spio species from the North and Baltic Seas consists of two median and two lateral bands of cilia (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Frequently reported from Greece and other parts of the Mediterranean (Castelli et al 2008, Çınar et al 2014. However, Meißner (2005) concluded that so far only specimens from the North Atlantic can be assigned to Spiophanes kroyeri. could only confirm the presence of Spiophanes afer Meißner, 2005 from the Adriatic Sea, whereas Spiophanes kroyeri could not be found.…”
Section: Spiophanes Kr Oyeri Grube 1860mentioning
confidence: 99%
“…However, Meißner (2005) concluded that so far only specimens from the North Atlantic can be assigned to Spiophanes kroyeri. could only confirm the presence of Spiophanes afer Meißner, 2005 from the Adriatic Sea, whereas Spiophanes kroyeri could not be found. Spiophanes afer is also known from the Turkish Aegean Sea and the Sea of Marmara (Dağli 2008.…”
Section: Spiophanes Kr Oyeri Grube 1860mentioning
confidence: 99%
See 1 more Smart Citation
“…Reported from Greece by NCMR (1989). Meißner (2005) restricts the distribution of the species to the Atlantic and Pacific coast of America and the Greek record is probably a misidentification.…”
Section: Checklistsmentioning
confidence: 99%